League of Coloured Peoples, 1945 (1945)
1945 1939-1945 "League of Coloured Peoples, 1945" [hfr0191], 1945 This extract from the 1944-45 annual report of the League of Coloured Peoples shows their concern over the racial discrimination faced in Britain by Black servicemen and workers from the Colonies, especially those from the West Indies. Dr Harold Moody, a Jamaican doctor, was President of the League of Coloured Peoples since its foundation in London in 1931 until his death in 1947. The height of the League's influence as a pressure group came in 1943, when it persuaded the Colonial Office to modify its own recruitment policy, even if only partially